Implementasi Diversi Pada Tahap Penuntutan Terhadap Anak Pelaku Tindak Pidana Di Kejaksaan Negeri Kabupaten Malang - Lantera Oase (Jurnal Hukum Lex Generalis, 2025)
The process of moving juvenile case settlements from the official legal system to an extrajudicial setting is known as diversion. This study's objectives were to assess the Malang Regency District Attorney's Office's diversion implementation. The study's findings show that the Malang Regency District Attorney's Office has applied diversion in compliance with legal requirements. Nevertheless, there are still a number of barriers to its implementation, including the dearth of child public prosecutors and the public's inadequate comprehension of the diversion concept. Consequently, it is essential to improve prosecutors' abilities and community awareness in order to provide. Thus, in order to promote the successful implementation of diversion in the future, it is imperative to enhance the competence of prosecutors and community socialization.